PERANCANGAN IKLAN TV DAIMA CULTURAL GARDEN RESTAURANT - DIDIT SETIAWAN, Drs. Syafwan, M.Si, Riri Trinanda, S.Pd., M.Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2015)
Daima Cultural Garden Restaurant is a restaurant in West Sumatra, especially in the city of desert that was established in 2005, which has a garden concept. Daima Cultural Garden Restaurant, located at Jl. Azizi No. 122 Sandalwood Complex Polamas Andalas Padang, West Sumatra, which was led by Mr. Doni Herlambang as the head of the Operational Manager Restaurant. From the start of the restaurant stood, a new campaign conducted through brochures, but still many people do not know it existed.Television is one of the effective medium, as in the delivery of informationthrough television ads more easily attract the attention of the target audience. The aim of the design is a television ad to promote a product, which is made in the form of video images and audio are equipped with television ads selected as the primary medium for this kind of information and technology is so easy to digest and is found by the target audience.Design method used is the SWOT analysis, the advantages of DaimaCultural Garden Restaurant is where the only restaurant that uses the concept of outdoor garden gazebo that is not boring that directly comes with a fishing pond.In this era of technology and information that have been developed at thistime can be used as a promotional media Daima Cultural Garden Restaurant in the form of TV ads, in addition to the TV ad campaign as the main medium is equipped with media support, among others, Clothes, Books Menu, Pin, CD Labels, CD Cover, Flag Chain, Plate, Number table and X-Banner.Keyword: Television, Promotion, Daima Cultural Garden Restaurant